DEVELOPMENT OF THE ELECTRIC VEHICLE MARKET WITH A FOCUS ON SUSTAINABILITY - Dluhopolskyi, Oleksandr; Kolinets, Lesya; Ivashuk, Yurii; Lotysh, Oksana; Sovira, Yaroslav (Socio-economic relations in the digital society, 2024)
In recent years, the global transportation sector has witnessed a shift towards electric vehicles powered by renewable energy sources. Experts predict an increasing role for electric vehicles in leading economies due to the depletion of fossil fuels and the harmful emissions from internal combustion engines. The rise in energy prices and stringent environmental regulations further drive this transition. The main goal of the research work is to study the relationship between the production of electric cars, government subsidies, oil prices, GDP per capita and R&D investments. Correlation analysis was chosen as the main method, but a graphical method was also used for visualization. There is a strong positive correlation between the production of Tesla electric cars and the price of oil, indicating that higher oil prices make Tesla electric cars a more attractive, cost-effective, and environmentally friendly alternative to gasoline and diesel cars. Based on the conducted analyses, it can be emphasized that the global transition to the production and use of electric vehicles is a critically necessary response to climate change, the reduction of fossil fuel reserves, and the growing need for sustainable development. This transition helps increase energy efficiency, reduce dependence on oil, and improve air quality in cities by reducing emissions of harmful substances.